Pancreatic Heterotopia Mimicking Gall Bladder Polyp – A Case Report - Arunagiri, Varun; Ahmad, Abdulazeez (International Journal of Human and Health Sciences (IJHHS), 2026)
Heterotopic pancreas, is also known as ectopic pancreas, pancreatic Choristoma, pancreatic rest, and aberrant pancreas. Ectopic Pancreas is a rare congenital anomaly defined as normal pancreatic tissue located outside its normal anatomical site without anatomical, vascular and neural continuity with the pancreas in the retroperitoneum. The overall incidence of ectopic pancreas at different locations is in decimals. Its occurrence in the gallbladder is rare and rarely reported in the literature. Ectopic pancreatic tissues are usually identified in an alive individual during cholecystectomy for gallstones, acute or chronic cholecystitis, or gallbladder polyps. They do not have a specific symptom. However, they mimic the symptoms of gallstones and acute or chronic cholecystitis. The clinical significance of this pathology is unclear. In this case, we report a 36-year-old female who was suffering from right upper quadrant pain for a year, which had the characteristics of biliary colic. She had a planned laparoscopic cholecystectomy as a day case procedure. The gallbladder specimen showed there were no stones postoperatively, and the specimen was sent for histological examination. The histology report identified an ectopic pancreatic tissue in the neck of the gallbladder near the cystic duct. The histological confirmation revealed that the ectopic pancreas was mimicking a gallbladder polyp and was producing symptoms of biliary colic. International Journal of Human and Health Sciences Vol. 10 No. 01 Jan’26 Page: 61-63